L’assurance dans la tourmente - Parizeau, Robert (Assurances, 1996)
At the 35th annual meeting of the Association des intermédiaires en assurance de personnes du Québec, held last November, Mr. Robert Parizeau gave a general overview of the profound changes that have been affecting the insurance industry since 1980. The first part of his speech focused on government reforms, the global market and the emergence of new conglomerates. In the second part, the author looks at the immediate future: the arrival of banks in the insurance industry and the new challenges for intermediaries, such as direct marketing, new technology, employee training, target market strategies and new methods of distributing products and services. Mr. Parizeau states that the near future will not only bring much change for insurance intermediaries, but also new opportunities.